2021
DOI: 10.1055/a-1653-4699
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Dose Intravenous Thrombolysis for Acute Intermediate–High-risk Pulmonary Embolism: Rationale and Design of the Pulmonary Embolism International THrOmbolysis (PEITHO)-3 trial

Abstract: Intermediate high-risk pulmonary embolism (PE) is characterised by right ventricular (RV) dysfunction and elevated circulating cardiac troponin levels despite apparent haemodynamic stability at presentation. In these patients, full-dose systemic thrombolysis reduced the risk of haemodynamic decompensation or death but increased the risk of life-threatening bleeding. Reduced-dose thrombolysis may be capable of improving safety while maintaining reperfusion efficacy. The Pulmonary Embolism International Trial (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 46 publications
0
43
0
3
Order By: Relevance
“…Although a higher than expected proportion of our patients underwent systemic thrombolysis or other reperfusion procedures, their possible effect on the development of CTEPH after acute PE cannot be addressed by a study with an observational design and remains questionable, 39 awaiting the results of ongoing randomized controlled trials. 40 Finally, and although known pre-existing CTEPH was an exclusion criterion for FOCUS, we cannot exclude the possibility that some of the CTEPH cases diagnosed at follow-up may have already been present at baseline. Intensive research is ongoing in this field, and recent publications identified a number of radiological findings which, when sought and found in the computed tomography pulmonary angiography performed to diagnose acute PE, may increase the level of suspicion for pre-existing CTEPH and possibly help to modify the follow-up strategy.…”
Section: Discussionmentioning
confidence: 97%
“…Although a higher than expected proportion of our patients underwent systemic thrombolysis or other reperfusion procedures, their possible effect on the development of CTEPH after acute PE cannot be addressed by a study with an observational design and remains questionable, 39 awaiting the results of ongoing randomized controlled trials. 40 Finally, and although known pre-existing CTEPH was an exclusion criterion for FOCUS, we cannot exclude the possibility that some of the CTEPH cases diagnosed at follow-up may have already been present at baseline. Intensive research is ongoing in this field, and recent publications identified a number of radiological findings which, when sought and found in the computed tomography pulmonary angiography performed to diagnose acute PE, may increase the level of suspicion for pre-existing CTEPH and possibly help to modify the follow-up strategy.…”
Section: Discussionmentioning
confidence: 97%
“…Future high-quality evidence from randomized controlled trials is required to provide clarity regarding the optimal PE management in specific subgroups of patients, including (i) the efficacy and safety of various CDT therapies among each other and relative to ST, (ii) the best therapy dependent on the patient’s risk of mortality (intermediate vs. high), and (iii) the effect of PERT implementation on clinical outcomes. For example, the Pulmonary Embolism International THrOmbolysis (PEITHO)-3 study (NCT04430569) will investigate whether reduced-dose thrombolysis improves safety while maintaining reperfusion efficacy compared with standard heparin anticoagulation in 650 patients with intermediate-high-risk PE in a randomized, placebo-controlled, double-blind manner ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 However, ST in patients with intermediate-high risk PE patients remains controversial and continues to be investigated. 13 The PEITHO-3 (NCT04430569) is an ongoing randomized, placebo-controlled, double-blind, multicenter, multinational trial with long-term follow-up to compare the efficacy and safety of a reduced-dose systemic IV alteplase regimen with standard heparin anticoagulation. The study will enroll 659 intermediate-high-risk PE patients.…”
Section: S Truc Ture Fun C Tion and R Ati Onale For Pertsmentioning
confidence: 99%